Patients undergoing surgery of intracranial metastases have different outcomes based on their primary pathology. (1st December 2013) - Chaichana, Kaisorn L; Gadkaree, Shekhar; Rao, Karthik; Link, Thomas; Rigamonti, Daniele; Purtell, Michael; Browner, Ilene; Weingart, Jon; Olivi, Alessandro; Gallia, Gary; Bettegowda, Chetan; Brem, Henry; et al.
<x xml:space="preserve">Abstract</x> Objectives: Patients with a variety of different primary cancers can develop intracranial metastases. Patients who develop intracranial metastases are often grouped into the same study population, and therefore an understanding of outcomes for patients with different primary cancers remain unclear. Methods: Adults who underwent intracranial metastatic tumor surgery from 1997-2011 at a single institution were retrospectively reviewed. Primary pathologies were compared using Fisher's exact and Student's t-test, and Cox regression analysis was used to identify factors associated with survival. Results: About 708 patients underwent surgery during the reviewed period, where 269 (38%) had non-small cell lung cancer (NSCLC), 106 (15%) breast cancer (BC), 72 (10%) gastrointestinal (GI) cancers, 88 (12%) renal cell cancer (RCC), and 88 (12%) melanoma. The most notable differences were that NSCLC patients were older, BC younger, BC had more primary tumor control, and NSCLC less extracranial spread. BC had longer survival, RCC had longer local progression free survival (PFS), and NSCLC had longer distal PFS. The factors independently associated with survival for NSCLC (female, recursive partitioning analysis (RPA) class, primary tumor control, solitary metastasis, tumor size, adenocarcinoma, radiation, discharge to home), BC (age, no skull base involvement, radiation), GI cancer (age, RPA class, Karnofsky performance scale (KPS), lack of preoperative motor deficit, non-esophageal tumors, non-hemorrhagic tumors, avoidance of new deficits), melanoma (preoperative seizures, solitary metastasis, smaller tumor size, discharge to home, chemotherapy), and RCC (KPS, chemotherapy) were distinctly different. Discussion: These differences between patients with different primary cancers support the fact that patients with intracranial disease are not all the same and should be studied by their primary pathology.